A public‐good approach to environmental economy. (20th June 2018) - Choi, Jai‐Young; Yu, Eden S.H.
Abstract : This paper investigates the economic implications of environment in the 2 × 3 Heckscher–Ohlin model by expounding the multidimensional roles of the environment for the economy: as a public input used to produce goods and services; as a by‐product dependent on the composition of goods and services; and as a public good directly affecting social utility. It is shown that the sectoral environment‐output responses play a critical role for determining the economy's factor prices, outputs, employment, and welfare, and that, in a dynamically stable (unstable) environment, the optimal policy is free trade (a production tax‐cum‐subsidy scheme).